Address Terms in the Bolango Language in Tolondadu Village, Bolaang Uki District - Windriyanti Nupulo; Asna Ntelu; Ulfa Zakaria (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Previous studies have examined address systems in several Indonesian regional languages; however, systematic documentation of address terms in the Bolango language, particularly within the sociocultural context of Tolondadu Village, remains limited. This gap highlights the need for in-depth analysis to clarify the forms and communicative functions of Bolango address terms and to contribute to local language preservation efforts. This study aims to describe the types of address terms and their functions in the Bolango language. The theoretical framework employed is sociolinguistic theory, particularly Koentjaraningrat’s classification of address terms (in Karel, 2022:23), which categorizes address terms into three types: personal name address terms, kinship address terms, and non-kinship address terms. This research applies a qualitative descriptive method with a sociolinguistic approach. The data consist of spoken utterances containing address terms produced by the community of Tolondadu Village. The study involved 15 informants, consisting of native speakers representing family members, community leaders, religious figures, traditional authorities, and general community members. Data were collected through observation, in-depth interviews, listening, recording, note-taking, and documentation techniques. The findings indicate that address terms in the Bolango language consist of personal name address terms, kinship address terms, and non-kinship address terms. Kinship address terms are the most dominant and are frequently extended beyond biological relationships to express respect and solidarity. Non-kinship address terms are mainly used in religious, customary, and formal social domains. Furthermore, address terms function to express respect, intimacy, and politeness, as well as to initiate and maintain effective communication. Their use is strongly influenced by age, social status, and the social relationship between speakers and addressees. In conclusion, the Bolango language possesses a diverse and culturally embedded system of address terms that reflects social hierarchy, solidarity, and community values. This study contributes to sociolinguistic scholarship and supports the documentation and preservation of the Bolango language for future generations.